Vibrant memory scapes: Encountering memorials on unstable ground. (August 2021) - Senior, Kate; McDuie-Ra, Duncan
Abstract: This article uses walking ethnography to approach the memoryscape of Stockton, a peninsula settlement opposite the city of Newcastle, Australia. As new residents of the city, we walked the memoryscape of Stockton together and with friends and family seeking encounters with the material objects of local memory as an entry into place. Stockton's memoryscape is full of objects gravid with deeply localised meanings. In some cases, our encounters have stimulated inquiry into documented histories and stories behind the objects, however we remain primarily concerned with the prospects, and limitations, of encountering the memoryscape 'fresh'. From these experiences we adopt a three-part argument. First, Stockton's memoryscape exhibits a shared local identity based on defiance evident in three groups of memorial objects: (i) unintentional memorials created by the unstable landscape (ii) DIY memorials made by local residents, and (iii) monuments sanctioned by local authorities. Second, Stockton's memoryscape remains powerfully rooted in place. It is vibrant, defying digitisation, defying displacement and re-placement. Stockton's memorials and monuments need to be found, encountered, shared in situ on the unstable ground of ballast and sinking sand. Third, walking ethnography restricted to a bounded area, mode of mobility (walking), theme (memorials), and epistemology (encounter with objects) generates rich ethnographic material on place, even without expert knowledge of the past. These experiments in walking and encountering objects in the vernacular memoryscape animated our imagination even with only limited detail on what to remember and how to feel about it. This offers a contribution to interdisciplinary research on the affective power of found material objects in ethnographic analysis. Highlights: Experiment with the prospects and limitations of encountering the material objects of the memoryscape as strangers to place lacking expert knowledge of local history. Consider walking ethnography as a collaborative exercise as a way to capture multiple affective attunements. Place is projected through material objects grouped as: DIY memorials, sanctioned monuments, and unintended memorials created by the unstable landscape itself. Local memoryscapes are directed towards residents, yet with gentrification changing the demography, time separates the affective properties of the memoryscape from the place that generated it. The memoryscape is left open to new imaginations and interpretations (like ours), often flawed yet still gravid with the weight of the past as played out in place.